Analysis of Wakawondu Organic Rice Demand in the Bina Insan Cita Indonesia Cooperation (BICI) Baruga District Kendari City - Widia Wati; Surni Surni; Abdul Gafaruddin (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2023)
This study aims to Determine the factors influencing the demand for organic Wakawondu rice in the Cooperative Bina Insan Cita Indonesia (BICI) in Baruga District, Kendari City. Wakawondu organic rice is essential to research because it is one of Southeast Sulawesi's leading commodities, and no research has discussed organic Wakawondu rice. This research was conducted from June to August 2022 at the BICI Cooperative Office. The data collected in this study was collected using primary data and secondary data. Preliminary data were obtained from interviews using questionnaires with BICI cooperative members as consumers and several buyers of organic rice they met. The method of determining the sample is accidental sampling, with the number of cooperative members as many as 30 people who happen to be at the research location. The analysis used Multiple Linear Regression analysis with the Ln method (Natural logarithm). The results showed that the factors that had a significant effect simultaneously on the demand for Wakawondu organic rice in the Bina Insan Cita Indonesia Cooperative, Baruga District, Kendari City, were the price of organic rice, the price of non-organic rice (rice head ), income, number of family dependents and consumer tastes.